Long‐term cost‐effectiveness of cognitive behavioral therapy versus psychodynamic therapy in social anxiety disorder. Issue 12 (18th July 2016) - Egger, Nina; Konnopka, Alexander; Beutel, Manfred E.; Herpertz, Stephan; Hiller, Wolfgang; Hoyer, Juergen; Salzer, Simone; Stangier, Ulrich; Strauss, Bernhard; Willutzki, Ulrike; Wiltink, Joerg; Leibing, Eric; et al.
Abstract : Background: To determine the cost‐effectiveness of cognitive behavioral therapy (CBT) versus psychodynamic therapy (PDT) in the treatment of social anxiety disorder after a follow‐up of 30 months from a societal perspective. Methods: This analysis was conducted alongside the multicenter SOPHO‐NET trial; adults with a primary diagnosis of social anxiety disorder received CBT ( n = 209) or PDT ( n = 207). Data on health care utilization and productivity loss were collected at baseline, after 6 months (posttreatment), and three further follow‐ups to calculate direct and indirect costs. Anxiety‐free days (AFDs) calculated based on remission and response were used as measure of effect. The incremental cost‐effectiveness ratio (ICER) was determined. Net benefit regressions, adjusted for comorbidities and baseline differences, were applied to derive cost‐effectiveness acceptability curves. Results: In the descriptive analysis, the unadjusted ICER favored CBT over PDT and the adjusted analysis showed that CBT's cost‐effectiveness relative to PDT depends on the willingness to pay (WTP) per AFD. As baseline costs differed substantially the unadjusted estimates might be deceptive. If additional WTPs for CBT of €0, €10, and €30 were assumed, the probability of CBT being cost‐effective relative to PDT was 65, 83, and 96%. Direct costs increased compared to baseline across groups, whereas indirect costs did not change significantly. Results were sensitive to considered costs. Conclusions: If the society is willing to pay ≥€30 per additional AFD, CBT can be considered cost‐effective, relative to PDT, with certainty. To further increase the cost‐effectiveness more knowledge regarding predictors of treatment outcome seems essential.